사보니우스 소형풍력터빈 수치해석용 격자시스템 평가 - 김철규(Chul-kyu Kim); 이상문(Sang-moon Lee); 전석윤(Seok-yun Jeon); 윤준용(Joon-yong Yoon); 장춘만(Choon-man Jang) (한국수소 및 신에너지학회 논문집, 2016)
This paper presents the effect of a grid system on the performance of a small Savonius wind turbine installed side-by-side. Turbine performance is compared using three different grid systems; tetrahedral grid having a concentrated circular grid around turbine rotors, the tetrahedral grid having a concentrated rectangular grid around turbine rotors and the symmetric grid having a concentrated tetrahedral grid near the turbine rotor blades and a hexahedral grid. The commercial code, SC/Tetra has been used to solve the three-dimensional unsteady Reynolds-averaged Navier-Stokes analysis in the present study. The Savonius turbine rotor has a rotational diameter of 0.226m and an aspect ratio of 1.0. The distance between neighboring rotor tips keeps the same length of the rotor diameter. The variations of pressure and power coefficient are compared with respect to blade rotational angles and rotating frequencies of the turbine blade. Throughout the comparisons of three grid systems, it is noted that the symmetric grid having a concentrated tetrahedral grid near the turbine rotor blades and a hexahedral grid has a stable performance compared to the other ones.